44ª campanha de vacinação anual contra a raiva em cães e gatos no município de Botucatu – 2014 - Modolo, José Rafael [UNESP]; Victória, Cassiano [UNESP]; Provenci, Tânia Maria Martins [UNESP]; Silva, Luciana Fernandes Nonato da [UNESP]; Jorge, Carolina de Oliveira Arantes [UNESP]; Martins, Patrícia Andrade [UNESP]; Iais, Rodrigo; Silva, Valdinei Moraes Campanucci da; Babonni, Selene Daniela; Borba, Julia de Pinho [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
In 2014 they were vaccinated 13,288 dogs and 2072 cats. For that they were mounted 74 vaccination posts during the five-day campaign covering the entire urban area of Botucatu. Vaccination posts were composed of 3 or 5 students Course of Veterinary Medicine FMVZ, and 2 or 3 Environmental Health Workers of the Municipality of Botucatu. The extension of the fellows actively participated from the organization, through execution to project closure. Students in the 4th year of Veterinary Medicine Course FMVZ / Botucatu were able to experience the reality of activities Veterinary Public Health for the control of rabies in a municipality, a model that serves as the basis for any population control diseases and of interest to the Public health.

No ano de 2014 foram vacinados 13288 cães e 2072 gatos. Para isso foram montados 74 postos de vacinação durante os cinco dias de campanha, abrangendo toda área urbana do município de Botucatu. Os postos de vacinação foram compostos por 3 ou 5 alunos do Curso de Medicina Veterinária da FMVZ, e 2 ou 3 Agentes de Saúde Ambiental da Prefeitura Municipal de Botucatu. As as bolsistas de extensão participaram ativamente desde a organização, passando pela execução até o fechamento do projeto. Os alunos do 4º ano do Curso de Medicina Veterinária da FMVZ/Botucatu puderam vivenciar a realidade das atividades de Saúde Pública Veterinária para o controle da Raiva em um município, modelo que serve como base para o controle de quaisquer enfermidades populacionais e de interesse para a Saúde Pública.
Keywords: Veterinary public health; Rabies; Vaccination campaign; Saúde pública veterinária; Raiva; Campanha de vacinação